Inadvertent effects of various media on UTAR students' English proficiency & fluency - Ng, Chee Kwan (2023)
This study investigates the impact of various media on the fluency, and proficiency of English among UTAR students. In the context of Malaysia's growing emphasis on English language education and its relevance in an interconnected world, understanding the influence of media consumption becomes crucial. Through an exploration of various media platforms, including television shows, movies, social media, games and online resources, this research aims to offer insights into innovative language teaching strategies. The findings can inform educators to design more effective language learning experiences that cater to students' digital-oriented daily lifestyles. The study's outcomes hold the potential to foster a linguistically diverse and competent society, empowering graduates to excel in the global landscape.